Innovative modified T-shape oncoplastic technique for early-stage breast cancer: multicenter retrospective study - Shi, Wenjie; Li, Keqing; Wang, Wanwan; Shi, Xuefeng; Li, Zhongyi; Torres-de La Roche, Luz Angela; Xu, Kai; Zhuo, Rui (Frontiers in Oncology, 2024)
Inadequate tissue volume at the lower pole of the breast following tumor excision can compromise aesthetic outcomes when employing the conventional inverted-T reconstruction technique. With the aim of reducing postoperative deformities, we have refined this technique. In total, 104 patients underwent the T technique, while 32 underwent the modified T technique and 72 underwent the traditional T technique. In this study, we present the surgical outcomes of the modified T technique group and compare both surgical and oncological outcomes with those of the traditional T technique group. In the modified T technique group, the average tumor size was 23.34 mm, and the mean operation duration was 107.75 min, which was significantly shorter than that of the traditional T technique (p = 0.039). Additionally, the average blood loss was 95.93 mL, which was significantly lower than that of the traditional T technique (p = 0.011). Although complication rates did not differ significantly between the two groups (p = 0.839), the modified T technique yielded superior aesthetic outcomes compared to the traditional T technique (p = 0.019). Survival analysis indicated no significant difference in 5-year recurrence-free survival between the two groups, both before and after propensity score matching (p = 0.381 vs. p = 0.277). As part of our series of oncoplastic techniques for the lower breast quadrant, the modified inverted-T technique utilizes a cost-effective flap to address lower pole defects, mitigating deformities and restoring the breast's natural shape.